Más allá de la perspectiva crítica - Rodríguez Rodríguez, Alfonsa (Cuadernos de Trabajo Social, 2007)
In this article, the author seeks to transcend the classic critical perspective as it has been articulated in drawing on new theoretical perspectives (social constructionism and constructivism), results in proposals for what we have called a reflective framework for theory and professional practice. Lastly, possible application to immigrant families is viewed through the lense of these ideas.